1999
DOI: 10.1111/j.1541-0064.1999.tb01396.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Commercial Structure of Non‐metropolitan Urban Centres and Vacancy Rates

Abstract: Utilizing data from 100 percent store‐by‐store surveys of five local communities undertaken by student interns during July in 1995 and 1997, the commercial structures of five non‐metropolitan centres in Ontario – Sturgeon Falls, Port Hope, Collingwood, Cobourg, and Sault Ste. Marie — are established and compared. The surveys include information related to store type, space, specific location, and employment. Trends in vacancy rates for the major components of the commercial structure (downtowns, shopping centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Nevertheless, Carling et al [ 68 ] indicated that the majority of shopping activity has moved from downtown to edge-of-town, such that shopping activity there is now 10 times higher than that downtown. Hence, in many developed countries, suburban shopping centers have come to dominate the retail structure in metropolitan areas, resulting in the deterioration of Central Business Districts [ 18 ]. As the inner city regional commercial centers of Xita-Beishi, Beihang, and Tiexi mainly serve residents in the closely-surrounding areas, most residents prefer to travel to these regional commercial centers by low-carbon transport modes, with the exception of Xita-Beishi, a specialty business street including flower markets, birds, fish, art, and antiques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Carling et al [ 68 ] indicated that the majority of shopping activity has moved from downtown to edge-of-town, such that shopping activity there is now 10 times higher than that downtown. Hence, in many developed countries, suburban shopping centers have come to dominate the retail structure in metropolitan areas, resulting in the deterioration of Central Business Districts [ 18 ]. As the inner city regional commercial centers of Xita-Beishi, Beihang, and Tiexi mainly serve residents in the closely-surrounding areas, most residents prefer to travel to these regional commercial centers by low-carbon transport modes, with the exception of Xita-Beishi, a specialty business street including flower markets, birds, fish, art, and antiques.…”
Section: Resultsmentioning
confidence: 99%
“…The function of commercial centers is to supply goods and services to meet the needs and desires of the public [ 17 ]. In many advanced countries, one of the most marked changes in the spatial retail structure of cities since the beginning of the 20th century is decentralization [ 16 , 18 ]. On the one hand, China’s metropolises are following the same path, with suburban shopping malls, large supermarkets, and new formats to serve surrounding suburban residents [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another methodology commonly used in retail development literature employs a mixed methods approach to explore the dynamics of retail and the role it plays in the community. Statistical analysis of secondary data and qualitative interviews with stakeholders are used to either compare a small number of geographically-defined areas (Linovski, 2012;Yeates and Montgomery, 1999) or evaluate the impacts of a particular event within a single area (Crosby et al, 2005). The scale at which this research is done can vary quite significantly, from a street segment, to a neighbourhood, and finally to an entire city.…”
Section: Retail Developmentmentioning
confidence: 99%
“…In many Western cities where suburbanization has progressed over several decades, the retail structure in metropolitan areas has become dominated by suburban arterial strips and shopping malls [8]. In contrast, suburbanization in Chinese cities is still at a relatively early stage, and the commercial and service sectors remain in the center of the city, creating a strong accumulation effect of traffic [9,10].…”
Section: Introductionmentioning
confidence: 99%